Administrative responsibility for offenses in the field of self-regulating organizations of arbitration managers - S. V. Fomichenko (Гуманитарные и юридические исследования)
Introduction. Administrative responsibility in the field of self-regulating organizations of arbitration managers is a developing sub-institution in the general structure of administrative responsibility, being a relatively new phenomenon associated with the development of self-regulation in this area. It plays an important role in ensuring the rule of law in the activities of these organizations, contributing to the achievement of the goal of preventing the commission of new offenses in the field of insolvency (bankruptcy) and streamlining social ties in the considered segment of the economic field.   Materials and Methods. The research is based on the application of general scientific methodology (analysis, synthesis, system-structural method, dialectical method) and formal legal method. The use of these methods made it possible to identify the shortcomings of administrative and tort legislation, formulate proposals aimed at improving it. Materials of judicial practice, normative and scientific-theoretical sources were used to conduct the study.   Analysis. The main areas of analysis are the law enforcement practice of arbitration courts on the issues of reviewing rulings on cases of administrative offenses of self-regulating organizations of arbitration managers related to the terms of performance of their duties and the referral of candidates of arbitration managers to the court.   Results. The positions of arbitration courts that have developed on the issues of the deadlines for the fulfillment of certain duties by self-regulating organizations of arbitration managers should become a guideline for the law enforcement officer, indicating the correct options for their calculation. The improvement of the pedagogical institute of administrative responsibility of self-regulating organizations of arbitration managers may be associated with the exclusion from the administrative-tort legislation of provisions implying an assessment by officials of executive authorities of the quality of the administration of justice in arbitration cases.